1987
DOI: 10.1093/jac/20.3.313
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase of Pseudomonas pseudomallei and its contribution to antibiotic resistance

Abstract: beta-Lactamase production was examined in nine strains of Pseudomonas pseudomallei isolated from human, animal and environmental sources in Thailand and Hong Kong. All produced the same weakly inducible, membrane associated chromosomal cephalosporinase, which had a molecular weight of 29,500 and an isoelectric point of 7.4-7.7. The enzyme resembled the cefuroximases of Ps. cepacia and Proteus vulgaris, but differed from the Class I cephalosporinases typical of Ps. aeruginosa and most enterobacteria, in being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
5
22
1
1
Order By: Relevance
“…Functionally, the most important of these is the BushJacoby-Medeiros class 2e beta-lactamase BPS-1, encoded by the gene blaA (or penA; Ambler class A), which hydrolyzes most cephalosporins but is readily inhibited by clavulanate (91,274). Acquired resistance to beta-lactam antibiotics while on treatment with a beta-lactam-beta-lactamase inhibitor combination or ceftazidime resulted from three distinct phenotypic changes: derepression of the chromosomal enzyme, an insensitivity to inhibition by beta-lactamase inhibitors, and a betalactamase specific for ceftazidime (169).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Functionally, the most important of these is the BushJacoby-Medeiros class 2e beta-lactamase BPS-1, encoded by the gene blaA (or penA; Ambler class A), which hydrolyzes most cephalosporins but is readily inhibited by clavulanate (91,274). Acquired resistance to beta-lactam antibiotics while on treatment with a beta-lactam-beta-lactamase inhibitor combination or ceftazidime resulted from three distinct phenotypic changes: derepression of the chromosomal enzyme, an insensitivity to inhibition by beta-lactamase inhibitors, and a betalactamase specific for ceftazidime (169).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Many reports have described successful treatment using a combination of ␤-lactam antibiotics and a ␤-lactamase inhibitor, such as amoxicillin plus clavulanic acid (19). Livermore, et al described a clavulanic acid-inhibitable ␤-lactam resistance phenotype of B. pseudomallei (13), and recently, the cloning of B. pseudomallei class A and D ␤-lactamases has been reported (4,14). Godfrey et al described three different phenotypes of clinical isolates from three patients which had undergone antibiotic treatment, and demonstrated that the resistance was due to derepressed ␤-lactamase production and structural mutations in the enzyme (10).…”
mentioning
confidence: 99%
“…The new broad-spectrum quinolone antibiotics penetrate phagocytes well (32). In general, however, they have shown limited activity against P. pseudomallei in vitro (2,6,8,20,33,34 (22). The P-lactamase-producing strains in our study which were highly resistant to ticarcillin-clavulanate also had relatively high imipenem MICs (4 ,ug/ml).…”
Section: Discussionmentioning
confidence: 62%
“…Disk diffusion tests with 22 antibiotics were performed on 199 isolates of P. pseudomallei. These included 189 shiny, 6 mucoid, and 4 wrinkled yellow-to-white colony morphotypes of the organism.…”
Section: Resultsmentioning
confidence: 99%